RESEARCH ON ADAPTABILITY AND RELIABILITY OF DESIGN FORMULAS IN PRESSURE EQUIPMENT PRESSURE - LIU Cen; WU SengLin; YANG Fan; HONG Kai; ZHANG Shu; LIU XiaoNing (Jixie qiangdu)
In order to provide the basis for selecting suitable design formula of pressure equipment strength,and to establish the reliability method of pressure equipment strength design,the ratio of the flat winding vessel burst pressure actual value to the formula calculated value was considered as a random variable. applied mathematical statistics and probability theory,the validity and homogeneity of random variables statistical samples were discussed,the random variables distribution law was analyzed,the comparison method of random variables distribution parameters was constructed. The evaluation index and method of formulas engineering adaptability were established from two aspects of precision and stability. Taking 15 sets of flat winding simulation vessel burst pressure measured data and 5 sets of flat winding industrial scale vessel burst pressure measured data as examples,the distribution laws and parameters of the random variables corresponding to four burst pressure calculation formulas were analyzed and compared,the engineering adaptability of the corresponding formula was evaluated. The researching results show that:（ 1） When the confidence of both sides was 99%,4 formulas corresponding random variables statistical samples are effective and homogeneous; if the significance was 0. 05,the 3 random variables are basically accorded with normal distribution,when the confidence of both sides was 98%,the value interval of distribution parameters are obtained.（ 2） Of the three random variables that basically fit the normal distribution,there is no significant difference in the distribution parameters of two random variables,but there is significant difference with the distribution parameters of the other one.